PENERAPAN METODE PRAKTIKUM FERMENTASI VINEGAR PADA MATA KULIAH PENGANTAR BIOTEKNOLOGI DI PROGRAM STUDI PENDIDIKAN BIOLOGI UNIVERSITAS ISLAM BALITAR BLITAR - Anggraini, Dian Puspita; Agustina, Dwi Kameluh (Universitas Islam Balitar, 2019)
This research aims at investigating the implementation of laboratory work method of vinegar fermentation on students’ science process skill and learning outcomes. This research was conducted at the Biology laboratory of Balitar Islamic University in the academic year of 2017/2018. The sample of this study were 25 Biology students. This study adopted Pre Experimental Design One Shoot Case Study. Results of this study revealed that the highest aspect of the students’ science process skill was arranging report (3.98), whereas the lowest aspect was arranging hypothesis (3.46). The highest percentage of science process skill was 80% on average, with the highest average score of 80.3. Meanwhile, the lowest percentage of science process skill was 8% on average, with the average score of 58.50. The implementation of laboratory work method of vinegar fermentation in Introduction to Biotechnology course attained the success of ≥75%, indicating that the students’ science process skill was good. The method can be applied in other courses which need more laboratory works. This method is applicable to other variables, too.